From Farm-to-Fork: E. Coli from an Intensive Pig Production System in South Africa Shows High Resistance to Critically Important Antibiotics for Human and Animal Use - Shima E. Abdalla; Akebe Luther King Abia; Daniel G. Amoako; Keith Perrett; Linda A. Bester; Sabiha Y. Essack (MDPI AG, 2021)
Antibiotic resistance profiles of Escherichia coli were investigated in an intensive pig production system in the uMgungundlovu District, South Africa, using the 'farm-to-fork' approach. Four hundred seventeen (417) samples were collected from pig and pig products at different points (farm, transport, and abattoir). E. coli was isolated and enumerated using the Colilert® 18/Quanti-Tray® 2000 system. Ten isolates from each Quanti-tray were selected randomly and putatively identified on eosin methylene blue agar. Real-time PCR targeting the uidA gene was used to confirm isolates to the genus level. The Kirby-Bauer disc diffusion method was used to determine the isolates' antibiotic susceptibility profiles against 20 antibiotics. A total of 1044 confirmed E. coli isolates were obtained across the three critical points in the food chain. Resistance was observed to all the antibiotics tested with the highest and lowest rates obtained against tetracycline (88.5%) and meropenem (0.2%), respectively. Resistance was also observed to chloramphenicol (71.4%), ampicillin (71.1%), trimethoprim-sulfamethoxazole (61.3%), amoxicillin-clavulanate (43.8%), cephalexin (34.3%), azithromycin (23.9%), nalidixic acid (22.1%), cefoxitin (21.1%), ceftriaxone (18.9%), ciprofloxacin (17.3%), cefotaxime (16.9%), gentamicin (15.5%), cefepime (13.8%), ceftazidime (9.8%), amikacin (3.4%), piperacillin-tazobactam (1.2%), tigecycline (0.9%), and imipenem (0.3%). Multidrug resistance (MDR) was observed in 71.2% of the resistant isolates with an overall multiple antibiotic resistance (MAR) index of 0.25, indicating exposure to high antibiotic use environments at the farm level. A high percentage of resistance was observed to growth promoters and antibiotics approved for veterinary medicine in South Africa. Of concern was resistance to critically important antibiotics for animal and human use and the watch and reserve categories of antibiotics. This could have adverse animal and human health consequences from a food safety perspective, necessitating efficient antibiotic stewardship and guidelines to streamline antibiotic use in the food-animal production chain.